2017
DOI: 10.1183/13993003.01446-2016
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of COPD patients with a smoking history in Central and Eastern Europe: the POPE Study

Abstract: Chronic obstructive pulmonary disease (COPD) represents a major health problem in Central and Eastern European (CEE) countries; however, there are no data regarding clinical phenotypes of these patients in this region.Participation in the Phenotypes of COPD in Central and Eastern Europe (POPE) study was offered to stable patients with COPD in a real-life setting. The primary aim of this study was to assess the prevalence of phenotypes according to predefined criteria. Secondary aims included analysis of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
109
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 40 publications
13
109
1
4
Order By: Relevance
“…The aims of the present study were 1) to analyse the effects of applying the new GOLD 2017 recommendations on the distribution of the A-D groups, and 2) to foresee the possible implications of the new GOLD recommendations on the maintenance therapy for COPD. For this purpose, we used data from the POPE (Phenotypes of COPD in Central and Eastern Europe) study, which is an international, multicentre, observational and cross-sectional study of 3361 COPD subjects in 10 countries in Central and Eastern Europe (CEE) (ClinicalTrials.gov identifier NCT02119494) [3]. The study provided numerous data, including ABCD distribution based on the 2016 GOLD Report and the distribution of predefined clinical COPD phenotypes [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The aims of the present study were 1) to analyse the effects of applying the new GOLD 2017 recommendations on the distribution of the A-D groups, and 2) to foresee the possible implications of the new GOLD recommendations on the maintenance therapy for COPD. For this purpose, we used data from the POPE (Phenotypes of COPD in Central and Eastern Europe) study, which is an international, multicentre, observational and cross-sectional study of 3361 COPD subjects in 10 countries in Central and Eastern Europe (CEE) (ClinicalTrials.gov identifier NCT02119494) [3]. The study provided numerous data, including ABCD distribution based on the 2016 GOLD Report and the distribution of predefined clinical COPD phenotypes [3].…”
mentioning
confidence: 99%
“…For this purpose, we used data from the POPE (Phenotypes of COPD in Central and Eastern Europe) study, which is an international, multicentre, observational and cross-sectional study of 3361 COPD subjects in 10 countries in Central and Eastern Europe (CEE) (ClinicalTrials.gov identifier NCT02119494) [3]. The study provided numerous data, including ABCD distribution based on the 2016 GOLD Report and the distribution of predefined clinical COPD phenotypes [3]. Its rationale, organisational structure and methodology have been reported in more detail previously [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A series of validation studies has been conducted in different region, and showed some similar results, such as a relatively low number of category C patients, significant heterogeneity in prospective exacerbation rates in category D, no differences in the predictive value of mortality for GOLD 2011 and GOLD 2007, and a better predictive value of exacerbation for GOLD 2011 and GOLD 2007 [18]. KOBLIZEK et al [4] also compared Spanish phenotypes with GOLD categories (2011 version) and showed that the majority of frequent exacerbators were in category D regardless of the coexistence of chronic bronchitis, whereas 39% of non-exacerbators and 56% of those with ACOS were also in category D, indicating marked heterogeneity in this category. In the 2017 update of GOLD, lung function (GOLD stages 1-4) is considered independent of the assessment of GOLD categories A-D, the predictive values of which need to be validated [2].…”
mentioning
confidence: 88%
“…In this issue of the European Respiratory Journal, KOBLIZEK et al [4] report an international, multicentre, observational cross-sectional study of COPD subjects in ten Central and Eastern European Countries, the POPE study. 3362 Patients with COPD were recruited and stratified according to the phenotypes recommended by the Spanish and Czech COPD guidelines [5][6][7]: 63% were considered non-exacerbators (NON-AE); 20.4%, with asthma-COPD overlap syndrome (ACOS); 9.5%, frequent exacerbators with chronic bronchitis (AE-CB); and 6.9%, frequent exacerbators without chronic bronchitis (AE NON-CB).…”
mentioning
confidence: 99%